Pusat Tuisyen Pintar An Nur (M) Sdn Bhd / Muhammad Afwan Hakim Ismail - Ismail, Muhammad Afwan Hakim (2021)
I gladly present you my case study on entrepreneur competency. I have prepared this case study on Mr khairolfizal an entrepreneur and CEO of Pusat Tuisyen Pintar An Nur. This report is prepared to collect data and information about the entrepreneur himself and also the company he runs. Although the main target of this case study is to examinate and make a conclusion about the good entrepreneur, boss and leader. I am very grateful because you always help me and guide me to complete this case study perfectly. he is an entrepreneur as well as a good leader based on observations and data collections that have been collected during his interview on the basis of google form platform and WhatsApp application. many competencies in him as attached in the entrepreneurial competency’s column. The company that I choose to my assignment is Pusat Tuisyen Pintar An Nur. This company the company provides educational services to young people especially for those with problems in mathematics and arithmetic. This tuition centre located in Terengganu provides many types of benefits both to students and employees there as well.